Reduction of metal artifacts from unilateral hip arthroplasty on dual-energy CT with metal artifact reduction software. (July 2018) - Yue, Dong; Fan Rong, Cheng; Ning, Cai; Liang, Hu; Ai Lian, Liu; Ru Xin, Wang; Ya Hong, Luo
Background: The evaluation of hip arthroplasty is a challenge in computed tomography (CT). The virtual monochromatic spectral (VMS) images with metal artifact reduction software (MARs) in spectral CT can reduce the artifacts and improve the image quality. Purpose: To evaluate the effects of VMS images and MARs for metal artifact reduction in patients with unilateral hip arthroplasty. Material and Methods: Thirty-five patients underwent dual-energy CT. Four sets of VMS images without MARs and four sets of VMS images with MARs were obtained. Artifact index (AI), CT number, and SD value were assessed at the periprosthetic region and the pelvic organs. The scores of two observers for different images and the inter-observer agreement were evaluated. Results: The AIs in 120 and 140 keV images were significantly lower than those in 80 and 100 keV images. The AIs of the periprosthetic region in VMS images with MARs were significantly lower than those in VMS images without MARs, while the AIs of pelvic organs were not significantly different. VMS images with MARs improved the accuracy of CT numbers for the periprosthetic region. The inter-observer agreements were good for all the images. VMS images with MARs at 120 and 140 keV had higher subjective scores and could improve the image quality, leading to reliable diagnosis of prosthesis-related problems. Conclusion: VMS images with MARs at 120 and 140 keV could significantly reduce the artifacts from hip arthroplasty and improve the image quality at the periprosthetic region but had no obvious advantage for pelvic organs.